Graphene Tunable Plasmon–Phonon Coupling in Mid‐IR Complementary Metamaterial. Issue 5 (26th February 2018) - Chen, Nan; Hasan, Dihan; Ho, Chong Pei; Lee, Chengkuo
Abstract: Metamaterial‐based plasmonics has become an overwhelming research field due to its enormous potential and versatility in molecular sensing, imaging, and nonlinear optics. This work presents a new tunable plasmonic platform on which the metamaterial resonance is coupled with infrared vibrational bond in the presence of graphene electrostatic modulation. The maximum electric field enhancement factor induced by mode coupling is 14 and the quality factor (Q‐factor) of phonon mode is increased approximately by fourfold. The graphene electrostatic modulation based on the parallel‐plate capacitor configuration enables a wavelength shift of 1.57 nm V −1, resonance intensity and Q‐factor modulation depth of 103.34% and 70%, respectively. Metamaterial based plasmon polariton perfectly matched with phonon mode yields the highest Q‐factor of 40. However, this perfectly matched resonance appears to be prohibitively "switched off" in the electrostatic tuning, which is reported for the first time. Mode splitting investigation reveals the largest coupling strength of 8.1 meV (1.96 THz) that results in the insensitivity to the perturbation caused by graphene modulation. Finally, an averaged sensitivity of 1.677 µm RIU −1 and a tunable figure of merit are reported, depicting the versatility of this platform for multiplexed sensing applications in various conditions. Abstract : A tunable plasmonic platform that enables plasmon–phonon coupling in the presence of graphene electrostatic modulation at mid‐infrared is presented. The plasmon perfectly matches with phonon mode yielding the highest Q‐factor and the greatest insensitivity to the graphene electrostatic tuning, which is explained from mode splitting perspective. This platform also shows the potential in molecule sensing in experiment.